2018
DOI: 10.1080/17434440.2018.1462697
|View full text |Cite
|
Sign up to set email alerts
|

From portable dialysis to a bioengineered kidney

Abstract: Since the advent of peritoneal dialysis (PD) in the 1970s, the principles of dialysis have changed little. In the coming decades, several major breakthroughs are expected. Areas covered: Novel wearable and portable dialysis devices for both hemodialysis (HD) and PD are expected first. The HD devices could facilitate more frequent and longer dialysis outside of the hospital, while improving patient's mobility and autonomy. The PD devices could enhance blood purification and increase technique survival of PD. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 88 publications
(99 reference statements)
0
65
0
Order By: Relevance
“…The kidney has two mechanisms to excrete uremic toxins into the urine. Small water-soluble solutes (e.g., urea) are primarily eliminated by glomerular filtration and protein-bound uremic toxins (PBUTs) primarily by tubular secretion mediated by transporters, including organic anion transporters (OAT) and organic cation transporters (OCT) for removal of PBUTs [1][2][3]. Hemodialysis (HD) is a life-sustaining renal replacement therapy that partially replaces renal glomerular filtration, but not renal tubular function.…”
Section: Introductionmentioning
confidence: 99%
“…The kidney has two mechanisms to excrete uremic toxins into the urine. Small water-soluble solutes (e.g., urea) are primarily eliminated by glomerular filtration and protein-bound uremic toxins (PBUTs) primarily by tubular secretion mediated by transporters, including organic anion transporters (OAT) and organic cation transporters (OCT) for removal of PBUTs [1][2][3]. Hemodialysis (HD) is a life-sustaining renal replacement therapy that partially replaces renal glomerular filtration, but not renal tubular function.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, BM MSC-based regenerative medicine approaches are being developed to treat CKD, aiming to halt progression of fibrosis by vascular regeneration, stimulate kidney regeneration, or enhance immunomodulation after renal transplantation. These therapies include administration of cells or products secreted by cells [9][10][11]. BM MSCs are an effective treatment for CKD in a range of preclinical animal models [12].…”
Section: Introductionmentioning
confidence: 99%
“…FDA‐approved phase I/II clinical studies with a RAD suggested a potential added value of such a device in the treatment of critically ill subjects . The development, current status, and technical challenges of RADs have been extensively reviewed elsewhere . Unfortunately, the efficiency of current RADs is limited to short‐time extracorporeal applications.…”
Section: Introductionmentioning
confidence: 99%